Germline stem cell arrest inhibits the collapse of somatic proteostasis early in Caenorhabditis elegans adulthood. Issue 5 (28th June 2013) - Shemesh, Netta; Shai, Nadav; Ben‐Zvi, Anat
Summary: All cells rely on highly conserved protein folding and clearance pathways to detect and resolve protein damage and to maintain protein homeostasis (proteostasis). Because age is associated with an imbalance in proteostasis, there is a need to understand how protein folding is regulated in a multicellular organism that undergoes aging. We have observed that the ability of Caenorhabditis elegans to maintain proteostasis declines sharply following the onset of oocyte biomass production, suggesting that a restricted protein folding capacity may be linked to the onset of reproduction. To test this hypothesis, we monitored the effects of different sterile mutations on the maintenance of proteostasis in the soma of C. elegans . We found that germline stem cell (GSC) arrest rescued protein quality control, resulting in maintenance of robust proteostasis in different somatic tissues of adult animals. We further demonstrated that GSC‐dependent modulation of proteostasis requires several different signaling pathways, including hsf‐1 and daf‐16/kri‐1/tcer‐1, daf‐12, daf‐9, daf‐36, nhr‐80, and pha‐4 that differentially modulate somatic quality control functions, such that each signaling pathway affects different aspects of proteostasis and cannot functionally complement the other pathways. We propose that the effect of GSCs on the collapse of proteostasis at the transition to adulthood is due to a switch mechanism that links GSC status with maintenance of somatic proteostasis via regulation of the expression and function of different quality control machineries and cellular stress responses that progressively lead to a decline in the maintenance of proteostasis in adulthood, thereby linking reproduction to the maintenance of the soma.